Study on the damage effect of optical detector irradiated by CW laser. Issue 1 (July 2021) - Zhang, Peng; Zhang, Zhening
Abstract: In order to study the damage effect of continuous laser on optical detectors, an equivalent experimental method of laser irradiated optical detectors was designed and constructed in the laboratory. The damage mechanism and phenomenon of the laser are analyzed through experiments, and the power density of the laser to the target and the size of the saturated spot on the surface of the detector are measured, and the corresponding relationship between the saturation of a single pixel of the detector and the power of the laser to the target is obtained, which reveals the influence of laser power on detection The influence law of the interference characteristic of the device. The experimental results show that under the condition that the diameter of the laser beam and the distance to the target are the same, as the power of the laser to the target increases, the saturated spot size of the detector (that is, the number of saturated pixels) increases, and the saturated spot size increases with the power within the error range. The relationship is approximately linear; for a typical optical detector, the laser power at which the pixels are disturbed by saturation is a fixed value. Increasing the laser power can increase the number of saturated pixels, and the area disturbed by laser saturation is further expanded.